De l’expérience reconnue à l’expérience déniée - Guy Brucy (Cahiers de la Recherche sur l'Education et les Savoirs)
From the end of the 19th century to the 1970s, the recognition of work experience has been a subject of conflicting interpretations. While employers used experience only for their immediate needs, public authorities were opposed its reduction to its sole productive functions.Since the years 1980-2000, changes have affected the organisation of the labour and completely modified the way ‘experiential knowledge’ is mobilized. In order to obtain a diploma, employees are now invited to capitalise on their experience. This article questions these evolutions by wondering if in spite of the media and political celebration of experience, knowledge derived from work experience is not actually utterly denied.